Towards an Anticolonial Photovoice: A Research Practice Guide to Theoretical and Methodological Considerations - Jennifer Fricas (Journal of Participatory Research Methods)
Photovoice researchers must avoid an ahistorical application of the method by critically examining the implementation and dissemination of photovoice projects. Recognizing that photovoice is not automatically empowering and that dismantling power dynamics is an ongoing struggle requiring constant vigilance to ethical, methodological, and representational issues, I propose an anticolonial framework for photovoice, drawing on the work of anticolonial scholars. This approach acknowledges the legacies of colonialism and racism within health and research systems, an imperative for researchers working with Indigenous and marginalized communities. I address multiple phases of a photovoice project, problematizing power relations in each phase and suggesting how to anticolonially adapt theoretical orientations and methodological processes. Areas under-addressed in the photovoice literature, such as epistemic justice, recruitment power relations, decolonized concepts of rigor, problematization of pseudonyms/anonymizing, and cross-language research and writing, are discussed, interweaving analyses with practical guidance from and outcomes of my photovoice research with Indigenous and mestizo communities in Ecuador.